A polyether type super wear-resistant halogen-free flame-retardant TPU composite material and preparation method thereof
Through the use of porous Co-Mn-O nanomaterials, modified phytate-vanillin composites and calcium phosphate oligomers in polyether TPU composites, the migration and precipitation of halogen-free flame retardant materials are solved. and water solubility issues significantly improve the flame retardant and wear resistance of the material and extend the service life.
Patent Information
- Application Number
- CN202411430936.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Inorganic flame retardant materials are easily migrated and precipitated in polyether-type thermoplastic polyurethane elastomers, and the synergistic flame retardant effect of organic and inorganic flame retardant composites is poor; the water solubility of phytic acid causes flame retardant materials to absorb moisture, affecting polyether-type thermoplastic polyurethane The service life of elastomer composites.
The flame retardant performance is improved by synthesizing porous Co-Mn-O nanomaterials in situ on the surface of hydroxylated calcium sulfate whiskers; the silicone composite is grafted in the phytic acid-vanillin complex and the phytic acid- Vanillin complex adsorbed into the pores of Co-Mn-O nanomaterials in modified calcium sulfate whiskers, forming an organic-inorganic flame retardant material with modified calcium sulfate whiskers; pretreated wear-resistant bones by isocyanate silane grafting The surface of the material improves wear resistance; the calcium phosphate oligomer and the molecular chain of the polyether TPU composite material are bonded through hydrogen bonding to form a crosslinking network structure, which improves the crosslinking density and wear resistance.
It significantly improves the flame retardant and wear resistance of polyether TPU composite materials, avoids the migration and precipitation and water solubility of halogen-free flame retardant materials, extends the service life of the material, and improves its stability in humid environments. sex.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyether TPU plastic processing, in particular to a polyether super wear-resistant halogen-free flame-retardant TPU composite material and a preparation method thereof. Background Art
[0002] Thermoplastic polyurethane elastomers (TPU) are divided into two categories: polyester type and polyether type. Polyether thermoplastic polyurethane elastomers are linear block copolymers composed of soft segment polyether polyols, diisocyanates, and chain extender hard segments. Polyether thermoplastic polyurethane elastomers can be plasticized after heating and have excellent processing properties. At the same time, they have excellent comprehensive properties such as high strength, high toughness, wear resistance, and oil resistance. They have good processing properties and are widely used in automobiles, coatings, national defense, building materials, clothing, wires and cables and other industries. The limiting oxygen index (LOI) of thermoplastic polyurethane elastomers is only about 19%, which affects their application in some fields with high fire safety requirements such as cables.
[0003] Thermoplastic polyurethane elastomers have poor flame retardant properties, dripping occurs during combustion, and are accompanied by thick black smoke. In addition, polyurethane materials produce harmful gases at high temperatures, causing environmental pollution. Adding inorganic and organic flame retardant materials to polyether thermoplastic polyurethane elastomers can effectively improve the flame retardant properties of the composite material, but inorganic flame retardant materials are easy to migrate and precipitate in polyether thermoplastic polyurethane elastomers, and the synergistic flame retardant effect of organic and inorganic flame retardant composite materials is poor. Phytic acid and vanillin, as bio-based flame retardants, have good flame retardant effects, but the water solubility of phytic acid causes the flame retardant material to be easy to absorb moisture, affecting the service life of the polyether thermoplastic polyurethane elastomer composite material. Summary of the invention
[0004] The invention aims to provide a polyether type super wear-resistant halogen-free flame-retardant TPU composite material and a preparation method thereof: in-situ synthesizing a Co-Mn-O nanomaterial with a porous structure on the surface of a hydroxylated calcium sulfate whisker, wherein the hydroxylated calcium sulfate whisker is used as a carrier of the Co-Mn-O nanomaterial, has an excellent aspect ratio, can load more Co-Mn-O nanomaterials, and improves the flame retardant performance; an organic silicon composite is grafted into a phytic acid-vanillin composite to improve the hydrophobicity of the phytic acid-vanillin composite, and avoids the high water solubility of phytic acid in the phytic acid-vanillin composite and easy water absorption; and the modified phytic acid-vanillin composite is adsorbed into the pores of the Co-Mn-O nanomaterial in the modified calcium sulfate whisker. , and form an organic-inorganic flame retardant material with modified calcium sulfate whiskers to improve flame retardant properties; the monomer formed by the reaction of dicyandiamide and adiponitrile is grafted on the surface of the pretreated wear-resistant aggregate through isocyanate silane, and the amino group contained in the monomer can be combined with the polyether TPU molecular chain through hydrogen bonds, so that the wear-resistant aggregate is evenly dispersed in the polyether TPU composite material, avoiding the migration and precipitation of the wear-resistant aggregate; the calcium phosphate oligomer can be combined with the polyether TPU composite material molecular chain through hydrogen bonds to form a cross-linked network structure, thereby increasing the cross-linking density of the polyether TPU composite material, making the polyether TPU composite material more compact, increasing the dissipation effect of external force, having excellent resistance to dynamic friction, and improving wear resistance.
[0005] The technical problem to be solved by the present invention is as follows: inorganic flame retardant materials are easy to migrate and precipitate in polyether thermoplastic polyurethane elastomers, and the synergistic flame retardant effect of organic and inorganic flame retardant composite materials is poor; phytic acid and vanillin, as bio-based flame retardants, have good flame retardant effects, but the water solubility of phytic acid causes the flame retardant materials to be easy to absorb moisture, affecting the service life of the polyether thermoplastic polyurethane elastomer composite material.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A polyether type super wear-resistant halogen-free flame-retardant TPU composite material comprises the following raw materials in parts by weight: 90-110 parts of a polyether type thermoplastic polyurethane elastomer, 10-15 parts of a composite flame-retardant filler, 10-12 parts of a composite wear-resistant aggregate, 1-2 parts of a compatibilizer, 0.1-0.5 parts of an ultraviolet absorber, and 0.2-0.6 parts of an antioxidant.
[0008] A method for preparing a polyether-type super wear-resistant halogen-free flame-retardant TPU composite material comprises the following steps:
[0009] S1. Place polyether thermoplastic polyurethane elastomer, composite flame retardant filler, composite wear-resistant aggregate, bulking agent, antibacterial agent, ultraviolet absorber and antioxidant in a mixer, and mix at high speed for 3-5 minutes at 40-60° C. to obtain a mixture.
[0010] S2. The mixed material is placed in a twin-screw extruder, and after extrusion and granulation, a polyether-type ultra-wear-resistant halogen-free flame-retardant TPU composite material is obtained.
[0011] Furthermore, the compatibilizer is a hydroxyl-terminated polyether-modified silicone oil, preferably XIAMETER OFX-3667.
[0012] Furthermore, the antioxidant is selected from any one of antioxidant 300, antioxidant 168, antioxidant 1010, and antioxidant 626.
[0013] Furthermore, the ultraviolet absorber is selected from any one of ultraviolet absorber UV-P, ultraviolet absorber UV-O, ultraviolet absorber UV-9 and ultraviolet absorber UV-531.
[0014] Furthermore, the twin-screw extruder process is as follows: the temperature of the twin-screw feeding zone is 180-190°C, the temperature of the plasticizing zone is 190-200°C, the head temperature is 200-210°C, and the screw speed is 70-90rpm.
[0015] Furthermore, the composite flame retardant filler is prepared by reacting phytic acid, vanillin, and an organic silicon compound, and then mixing with modified calcium sulfate whiskers, and is specifically prepared by the following steps:
[0016] A1. Add vanillin to ethanol, stir evenly, add phytic acid, 4-xylenepyridine with a concentration of 4 g / L and N,N-dicyclohexylcarbodiimide, stir and react at 130°C for 3 hours, filter, wash with deionized water 3 times, and dry in an oven at 80°C for 10 minutes to obtain a phytic acid-vanillin complex.
[0017] Among them, 4-xylene pyridine is used as a catalyst to enable the phosphorus hydroxyl group contained in phytic acid to react with the hydroxyl group of vanillin, and N,N-dicyclohexylcarbodiimide is used as a water absorbent to absorb the water molecules produced by the reaction of phytic acid and vanillin to form a phytic acid-vanillin complex. The phytic acid-vanillin complex can catalyze carbonization and form an organic-inorganic flame retardant material with modified calcium sulfate whiskers to improve the flame retardant properties.
[0018] Furthermore, the usage ratio of vanillin, ethanol, phytic acid, 4-xylenepyridine and N,N-dicyclohexylcarbodiimide is (7.2-7.4) g:(35-45) mL:(13-17) g:(0.1-0.3) g:(1.5-1.7) g.
[0019] A2. Add the phytic acid-vanillin complex to deionized water and ethanol, stir evenly, add the organosilicon complex and a 36% sodium hydroxide solution by mass to adjust the pH to 4.5, heat to 80°C, stir and react for 1 hour, cool to room temperature, remove ethanol by concentration and evaporation, filter, wash with deionized water 3 times, and dry in an oven at 80°C for 10 minutes to obtain the phytic acid-vanillin complex.
[0020] Among them, at 80°C and alkaline conditions, the aldehyde group of vanillin in the phytic acid-vanillin complex can undergo a Schiff base reaction with the amino group in the silicone complex, and the silicone complex is grafted into the phytic acid-vanillin complex to form a modified phytic acid-vanillin complex, thereby improving the hydrophobic properties of the phytic acid-vanillin complex and avoiding the high water solubility of phytic acid in the phytic acid-vanillin complex, which is easy to absorb water and affects the stability and service life of the polyether TPU composite material in a humid environment.
[0021] Furthermore, the dosage ratio of phytic acid-vanillin complex, deionized water, ethanol, and organosilicon complex is (4-6) g: (70-90) mL: (15-25) mL: (6-7) g.
[0022] A3. Add the modified phytic acid-vanillin complex to ethanol, stir, add modified calcium sulfate whiskers, under negative pressure of -0.1 MPa for 10 minutes, heat to 85°C, stir until ethanol evaporates, wash with deionized water three times, and dry in an oven at 80°C for 10 minutes to obtain a composite flame retardant filler.
[0023] Among them, the porous structure of the Co-Mn-O nanomaterial in the modified calcium sulfate whisker has good adsorption performance, and can adsorb the modified phytic acid-vanillin complex into the pores of the Co-Mn-O nanomaterial in the modified calcium sulfate whisker, so that the organic flame retardant material modified phytic acid-vanillin complex and the inorganic flame retardant modified calcium sulfate whisker are precisely combined to improve the flame retardant performance.
[0024] It should also be noted that during the combustion process, the modified phytic acid-vanillin complex is thermally decomposed and detached from the pores of the Co-Mn-O nanomaterial, which does not affect the adsorption and smoke suppression performance of the Co-Mn-O nanomaterial.
[0025] Furthermore, the usage ratio of the modified phytic acid-vanillin complex, ethanol, and modified calcium sulfate whiskers is (2-3) g:(25-35) mL:(0.2-0.4) g.
[0026] Furthermore, the organosilicon composite is specifically prepared by the following steps:
[0027] N-aminoethyl-3-aminopropylmethyldimethoxysilane and octamethylcyclotetrasiloxane were mixed and stirred evenly, and sodium hydroxide, deionized water and sodium dodecylbenzenesulfonate were added. After stirring and reacting at 80° C. for 5 hours, the temperature was lowered to 40° C., and 36% hydrochloric acid was added to adjust the pH to neutral. The filtrate was collected by filtration to obtain an organosilicon composite.
[0028] Among them, sodium hydroxide is used as a catalyst and sodium dodecylbenzene sulfonate is used as an emulsifier to make N-aminoethyl-3-aminopropylmethyldimethoxysilane react with octamethylcyclotetrasiloxane, and N-aminoethyl-3-aminopropylmethyldimethoxysilane is grafted on the octamethylcyclotetrasiloxane to obtain amino-modified silicone.
[0029] Furthermore, the dosage ratio of N-aminoethyl-3-aminopropylmethyldimethoxysilane, octamethylcyclotetrasiloxane, sodium hydroxide, deionized water, and sodium dodecylbenzenesulfonate is (4-5) g: (5-6) g: (0.01-0.03) g: (8-12) mL: (0.4-0.6) g.
[0030] Furthermore, the modified calcium sulfate whisker is prepared by mixing hydroxylated calcium sulfate whisker with a cobalt source and a manganese source and then calcining the mixture.
[0031] Furthermore, the length of the hydroxylated calcium sulfate whiskers is 12-26 μm and the diameter is 0.5-1.5 μm.
[0032] Furthermore, the manganese source is selected from manganese sulfate hydrate or manganese nitrate.
[0033] Further, the cobalt source is selected from cobalt sulfate heptahydrate or cobalt nitrate.
[0034] Furthermore, the calcination temperature is 450-550° C., and the calcination time is 3-5 h.
[0035] Further, the modified calcium sulfate whisker is specifically prepared by the following steps:
[0036] Add cobalt source and manganese source to ethanol and deionized water, stir evenly, add hydroxylated calcium sulfate whiskers, stir for 10 minutes, add sodium carbonate aqueous solution with a concentration of 0.4-0.6 mol / L until the pH is 8.5, keep overnight, filter, wash with deionized water 3 times, dry in an oven at 80°C for 5 hours, place in a Ma furnace, roast at 500°C for 4 hours, cool to room temperature, and obtain modified calcium sulfate whiskers.
[0037] The hydroxyl groups on the surface of the hydroxylated calcium sulfate whiskers can combine with the cobalt ions and manganese ions in the cobalt source and the manganese source, so that the cobalt source and the manganese source are deposited on the surface of the hydroxylated calcium sulfate whiskers, and sodium bicarbonate, as a precipitant, can combine with the cobalt ions and manganese ions deposited on the surface of the hydroxylated calcium sulfate whiskers to form carbonate precipitates.
[0038] Furthermore, high-temperature calcination is carried out at 500° C., and the carbonate precipitate is thermally decomposed to form metal oxide cobalt oxide. During the calcination process, manganese partially replaces cobalt in the cobalt oxide lattice, so that manganese is incorporated into the lattice of the metal oxide cobalt oxide to form a Co-Mn-O nanomaterial. In addition, the carbonate precipitate produces gas release during thermal decomposition to form a porous Co-Mn-O nanomaterial, thereby achieving in-situ synthesis of a porous Co-Mn-O nanomaterial on the surface of the hydroxylated calcium sulfate whisker.
[0039] Furthermore, the usage ratio of cobalt source, manganese source, ethanol, deionized water, and hydroxylated calcium sulfate whisker is (1.3-1.34) g: (0.5-0.7) g: (16-20) mL: (170-190) mL: (2-3) g.
[0040] Furthermore, the pore size of the porous Co-Mn-O nanomaterial is 30-50 nm.
[0041] Further, the hydroxylated calcium sulfate whiskers are specifically prepared by the following steps:
[0042] The hydroxylated calcium sulfate whisker is prepared by the following steps: adding the calcium sulfate whisker into a sodium phosphate tribasic solution with a concentration of 0.02-0.03 mol / L, ultrasonically treating, stirring evenly, filtering, washing and drying to obtain the hydroxylated calcium sulfate whisker.
[0043] Among them, the calcium sulfate whiskers are surface-treated with trisodium phosphate, so that the surface of the calcium sulfate whiskers carries a large number of hydroxyl groups, the surface polarity of the calcium sulfate whiskers is improved, and the calcium sulfate whiskers are not affected by the external environment and undergo crystal transformation.
[0044] Furthermore, the dosage ratio of calcium sulfate whisker to trisodium phosphate solution is (2-3) g: (80-120) mL.
[0045] Furthermore, the composite wear-resistant aggregate is prepared by mixing modified wear-resistant aggregate and calcium phosphate oligomer, and is specifically prepared by the following steps:
[0046] Phosphoric acid is added to ethanol and stirred to obtain a phosphoric acid ethanol solution, calcium chloride dihydrate is added to ethanol, stirred at 25°C for 30 minutes, triethylamine is added and stirred for 10 minutes, phosphoric acid ethanol solution is added, stirred and reacted for 12 hours, and then the precipitate is collected by centrifugation at 8000 rpm, the precipitate is washed three times with ethanol to remove triethylamine, and added to ethanol to form a stable emulsion to obtain calcium phosphate oligomer, the calcium phosphate oligomer and modified wear-resistant aggregate are mixed, and stirred evenly to obtain composite wear-resistant aggregate.
[0047] Among them, the phosphate in the ethanol phosphoric acid solution can combine with the modified calcium ions in the calcium chloride dihydrate to form calcium phosphate oligomers. The calcium phosphate oligomers are amorphous and gel-like structures, which can combine with the polyether TPU molecular chains through hydrogen bonds to form a cross-linked network structure, thereby increasing the cross-linking density of the polyether TPU composite material, making the polyether TPU composite material more compact, increasing the dissipation effect of external forces, and having excellent resistance to dynamic friction.
[0048] Furthermore, the cross-linked network structure formed by the calcium phosphate oligomer and the polyether TPU can encapsulate the modified wear-resistant aggregate in the polyether TPU composite material, thereby improving the bonding force of the composite wear-resistant aggregate in the polyether TPU composite material and improving the high wear resistance of the polyether TPU composite material.
[0049] Furthermore, the ratio of phosphoric acid to ethanol is (2-3) g:(25-35) mL.
[0050] Furthermore, the dosage ratio of calcium chloride dihydrate, ethanol, triethylamine and phosphoric acid ethanol solution is (0.4-0.5) g: (50-70) mL: (6-6.2) g: (25-35) mL.
[0051] Furthermore, the mass ratio of calcium phosphate oligomer and modified wear-resistant aggregate is (25-35):(2-3).
[0052] Furthermore, the modified wear-resistant aggregate is prepared by reacting dicyandiamide and adiponitrile to form a monomer, which is then mixed with the wear-resistant aggregate surface-treated with isocyanate silane for reaction.
[0053] Furthermore, the isocyanate silane is selected from 3-isocyanate propyl trimethoxy silane or isocyanate propyl triethoxy silane.
[0054] Furthermore, the wear-resistant aggregate is selected from any one of nano-alumina, nano-calcium silicate, nano-zirconium oxide, nano-calcium carbonate, nano-silicon carbide and nano-silicon dioxide.
[0055] Furthermore, the wear-resistant aggregate has a particle size of 100-300 nm.
[0056] Further, the modified wear-resistant aggregate is specifically prepared by the following steps:
[0057] B1. Add dicyandiamide and potassium hydroxide to 2-methoxyethanol, stir at 200 rpm for 10 min, add adiponitrile, raise the temperature to 125°C, stir and react for 6 h, filter the mixture and wash with methanol to obtain a reaction product, and dry the reaction product in a vacuum oven at 80°C and 10 Pa for 24 h to obtain a monomer.
[0058] Among them, 2-methoxyethanol is used as a solvent, potassium hydroxide is used as a catalyst, and the reaction is stirred at 125°C to make dicyandiamide react with adiponitrile to obtain a monomer. The synthesis steps are as follows:
[0059]
[0060] Furthermore, the usage ratio of dicyandiamide, potassium hydroxide, 2-methoxyethanol and adiponitrile is (4-6) g:(1-2) g:(45-55) mL:(2.5-2.9) mL.
[0061] B2. Add wear-resistant aggregate and isocyanate silane to ethanol and deionized water, stir evenly, adjust the pH to 4 with 36% hydrochloric acid, stir and react at 40°C for 10 minutes, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain pretreated wear-resistant aggregate.
[0062] Among them, the hydroxyl groups generated by the hydrolysis of isocyanate silane can be combined with the hydroxyl groups on the surface of the wear-resistant aggregate through chemical bonds, so that the isocyanate silane is grafted on the surface of the wear-resistant aggregate.
[0063] Furthermore, the usage ratio of wear-resistant aggregate, isocyanate silane, ethanol and deionized water is (0.3-0.7) g: (0.4-0.5) g: (15-25) mL: (6-10) mL.
[0064] B3. Add the monomer to N-methyl-2-pyrrolidone, stir evenly, add trifluoroacetic acid to promote the dissolution of the monomer, heat to 80°C, add pretreated wear-resistant aggregate, stir and react for 3 hours, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain modified wear-resistant aggregate.
[0065] Among them, N-methyl-2-pyrrolidone is used as a solvent, and the amino group contained in the monomer can react with the isocyanate group contained in the surface of the pretreated wear-resistant aggregate, so that the monomer is grafted on the surface of the pretreated wear-resistant aggregate to form a modified wear-resistant aggregate. The amino group contained in the monomer in the modified wear-resistant aggregate can be combined with the polyether TPU molecular chain through hydrogen bonds, so that the wear-resistant aggregate is evenly dispersed in the polyether TPU composite material, avoiding the migration and precipitation of the wear-resistant aggregate, and improving the wear resistance. The triazine ring structure contained in the monomer in the modified wear-resistant aggregate increases the stiffness of the molecular chain of the polyether TPU composite material and improves the mechanical properties.
[0066] Furthermore, the usage ratio of the monomer, N-methyl-2-pyrrolidone, trifluoroacetic acid, and pretreated wear-resistant aggregate is (2-3) g:(15-25) mL:(0.1-0.3) mL:(0.3-0.7) g.
[0067] Furthermore, compared with the prior art, the present invention has the following beneficial effects:
[0068] (1) In the technical solution of the present invention, the porous structure of the Co-Mn-O nanomaterial has excellent catalytic carbonization performance, thereby isolating oxygen and heat and having good flame retardant properties. The porous structure of the Co-Mn-O nanomaterial can effectively adsorb harmful gases in the combustion process of the polyether TPU composite material and inhibit the generation of smoke. In addition, the Co-Mn-O nanomaterial can effectively catalyze the harmful gases released during the combustion of the polyether TPU composite material and convert the harmful gases into CO2, thereby inhibiting the generation of smoke and harmful gases.
[0069] (2) In the technical scheme of the present invention, a porous Co-Mn-O nanomaterial is synthesized in situ on the surface of hydroxylated calcium sulfate whiskers. The hydroxylated calcium sulfate whiskers serve as carriers of the Co-Mn-O nanomaterials and have an excellent aspect ratio, and can load more Co-Mn-O nanomaterials, thereby improving the flame retardant properties. A rough surface is formed on the surface of the hydroxylated calcium sulfate whiskers, thereby increasing the contact area between the composite flame retardant filler and the polyether TPU composite material, mechanically interlocking with the polyether TPU composite material, and improving the bonding force between the composite flame retardant filler and the polyether TPU composite material. In addition, the calcium sulfate whiskers in the composite flame retardant filler are randomly distributed, which can absorb external stress and improve the impact strength of the polyether TPU composite material.
[0070] (3) In the technical solution of the present invention, the phytic acid-vanillin complex is used as a bio-based flame retardant and can be used as a carbon-forming agent during the combustion process to generate an expanded carbon layer to isolate the combustible gas; the organosilicon complex is grafted into the phytic acid-vanillin complex to improve the hydrophobicity of the phytic acid-vanillin complex and avoid the high water solubility of phytic acid in the phytic acid-vanillin complex, which is easy to absorb water and affects the stability and service life of the polyether TPU composite material in a humid environment.
[0071] (4) In the technical scheme of the present invention, the modified phytic acid-vanillin complex is adsorbed into the pores of the Co-Mn-O nanomaterial in the modified calcium sulfate whisker to form an organic-inorganic flame retardant material with the modified calcium sulfate whisker, thereby improving the flame retardant performance. Phytic acid and vanillin provide more carbon sources, which is beneficial to the catalytic carbonization effect of the Co-Mn-O nanomaterial in the modified calcium sulfate whisker. In addition, the organic flame retardant material modified phytic acid-vanillin complex is precisely combined with the inorganic flame retardant modified calcium sulfate whisker to improve the flame retardant performance. In addition, the hydrophobic chain contained in the organosilicon complex in the modified phytic acid-vanillin complex can be combined with the hydrophobic chain segment of the polyether TPU composite material, thereby improving the compatibility of the composite flame retardant filler with the polyether TPU composite material, thereby improving the flame retardant performance and mechanical properties of the polyether TPU composite material.
[0072] (5) In the technical scheme of the present invention, the monomer formed by the reaction of dicyandiamide and adiponitrile is grafted onto the surface of the pretreated wear-resistant aggregate through isocyanate silane to form a modified wear-resistant aggregate. The amino group contained in the monomer in the modified wear-resistant aggregate can be combined with the polyether TPU molecular chain through hydrogen bonds, so that the wear-resistant aggregate is evenly dispersed in the polyether TPU composite material, avoiding the migration and precipitation of the wear-resistant aggregate, and improving the wear resistance. In addition, the triazine ring structure contained in the monomer in the modified wear-resistant aggregate increases the stiffness of the molecular chain of the polyether TPU composite material, thereby improving the mechanical properties.
[0073] (6) In the technical solution of the present invention, the calcium phosphate oligomer is amorphous and gel-like. The calcium phosphate oligomer can combine with the molecular chain of the polyether TPU composite material through hydrogen bonds to form a cross-linked network structure, thereby increasing the cross-linking density of the polyether TPU composite material, making the polyether TPU composite material more compact, increasing the dissipation effect of external force, having excellent resistance to dynamic friction, and improving wear resistance. The formed cross-linked network structure can encapsulate the modified wear-resistant aggregate and the composite flame retardant material in the polyether TPU composite material, thereby improving the flame retardancy and high wear resistance of the polyether TPU composite material. DETAILED DESCRIPTION
[0074] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0075] The raw materials used in the embodiments of the present invention are as follows:
[0076] Manganese sulfate hydrate, cobalt sulfate heptahydrate (purity 98%, Aladdin Biochemical Technology Co., Ltd.); dicyandiamide, adiponitrile, 2-methoxyethanol, trifluoroacetic acid (purity 99%, Shanghai Huayi Energy Chemical Co., Ltd.); 3-isocyanatepropyltrimethoxysilane (Shandong Lingxiao New Materials Co., Ltd.); N-methyl-2-pyrrolidone (Tianjin Komiou Chemical Reagent Co., Ltd.); phosphoric acid, calcium chloride dihydrate (China National Pharmaceutical Group Co., Ltd.); 4-xylenepyridine, vanillin (Shanghai Aladdin Biochemical Technology Co., Ltd., purity 99%); N,N-dicyclohexylcarbodiimide (Shanghai Aladdin Biochemical Technology Co., Ltd., purity 99%); N-aminoethyl-3-aminopropylmethyldimethoxysilane (Shanghai Guyan Industrial Co., Ltd., industrial grade); octamethylcyclotetrasiloxane (industrial grade, Hubei Kewode Chemical Co., Ltd.); phytic acid (Beijing Biolab Technology Co., Ltd.).
[0077] The compatibilizer is a hydroxyl-terminated polyether-modified silicone oil, preferably XIAMETER OFX-3667.
[0078] Calcium sulfate whiskers: length 12-30μm, diameter 0.5-2μm, Hubei Langbowan Biomedicine Co., Ltd.
[0079] Hydroxylated calcium sulfate whiskers are specifically prepared by the following steps:
[0080] 2.6 g of calcium sulfate whiskers were added to 100 mL of 0.025 mol / L trisodium phosphate solution, ultrasonically treated for 2 min, stirred at room temperature to mix the solution evenly, filtered, washed with deionized water 3 times, and dried in an oven at 80° C. for 10 min to obtain hydroxylated calcium sulfate whiskers.
[0081] The phytic acid-vanillin complex is specifically prepared by the following steps:
[0082] Add 7.3 g of vanillin to 40 mL of ethanol and stir evenly. Add 15 g of phytic acid, 0.2 g of 4-xylenepyridine with a concentration of 4 g / L and 1.6 g of N,N-dicyclohexylcarbodiimide. Stir and react at 130 ° C for 3 hours. Remove ethanol by concentration and evaporation, then filter, wash 3 times with deionized water, and dry in an oven at 80 ° C for 10 minutes to obtain a phytic acid-vanillin complex.
[0083] The organosilicon composite is specifically prepared by the following steps:
[0084] 4.5 g of N-aminoethyl-3-aminopropylmethyldimethoxysilane and 5.6 g of octamethylcyclotetrasiloxane were mixed and stirred evenly, 0.02 g of sodium hydroxide, 10 mL of deionized water and 0.5 g of sodium dodecylbenzenesulfonate were added, and the mixture was stirred and reacted at 80° C. for 5 h, then cooled to 40° C., 36% hydrochloric acid was added to adjust the pH to neutral, and the filtrate was collected by filtration to obtain an organosilicon composite.
[0085] Example 1 The composite flame retardant filler is specifically prepared by the following steps:
[0086] A1. Add 1.32 g of cobalt sulfate heptahydrate and 0.6 g of manganese sulfate hydrate to 18 mL of ethanol and 180 mL of deionized water, stir evenly, add 2.6 g of hydroxylated calcium sulfate whiskers, stir for 10 min, add 0.5 mol / L sodium carbonate aqueous solution until the pH is 8.5, keep overnight, filter, wash with deionized water 3 times, dry in an oven at 80°C for 5 h, place in a Mabo furnace, roast at 500°C for 4 h, and cool to room temperature to obtain modified calcium sulfate whiskers.
[0087] A2. Add 5 g of phytic acid-vanillin complex to 80 mL of deionized water and 20 mL of ethanol, stir evenly, add 6.5 g of organosilicon complex and 36% sodium hydroxide solution to adjust the pH to 4.5, heat to 80°C, stir to react for 1 hour, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80°C for 10 minutes to obtain a modified phytic acid-vanillin complex.
[0088] A3. Add 2.5 g of modified phytic acid-vanillin complex to 30 mL of ethanol, stir, add 0.3 g of modified calcium sulfate whisker, under negative pressure of -0.1 MPa for 10 min, heat to 85°C, stir until ethanol evaporates, wash with deionized water 3 times, and dry in an oven at 80°C for 10 min to obtain a composite flame retardant filler.
[0089] Comparative Example 1 The difference between this comparative example and Example 1 is that the Co—Mn—O nanomaterial is not synthesized on the surface of the calcium sulfate whisker, and the remaining steps and raw materials are the same as those in Example 1.
[0090] A1. Add 5 g of phytic acid-vanillin complex to 80 mL of deionized water and 20 mL of ethanol, stir evenly, add 6.5 g of organosilicon complex and 36% sodium hydroxide solution to adjust the pH to 4.5, heat to 80°C, stir to react for 1 hour, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80°C for 10 minutes to obtain a modified phytic acid-vanillin complex.
[0091] A2. Add 2.5 g of modified phytic acid-vanillin complex to 30 mL of ethanol, stir, add 0.3 g of calcium sulfate whisker, heat to 85°C, stir until ethanol evaporates, and obtain a composite flame retardant filler.
[0092] Comparative Example 2 The difference between this comparative example and Example 1 is that no modified phytic acid-vanillin complex is added, and the remaining steps and raw materials are the same as those in Example 1.
[0093] Add 1.32 g of cobalt sulfate heptahydrate and 0.6 g of manganese sulfate hydrate to 18 mL of ethanol and 180 mL of deionized water, stir evenly, add 2.6 g of hydroxylated calcium sulfate whiskers, stir for 10 min, add 0.5 mol / L sodium carbonate aqueous solution until the pH is 8.5, keep overnight, filter, wash 3 times with deionized water, dry in an oven at 80 ° C for 5 h, place in a Ma furnace, roast at 500 ° C for 4 h, cool to room temperature, and obtain a composite flame retardant filler.
[0094] Example 2
[0095] The composite wear-resistant aggregate is specifically prepared by the following steps:
[0096] B1. Add 5 g of dicyandiamide and 1.5 g of potassium hydroxide to 50 mL of 2-methoxyethanol, stir at 200 rpm for 10 min, add 2.7 mL of adiponitrile, raise the temperature to 125°C, stir and react for 6 h, filter the mixture and wash with methanol to obtain a reaction product, and dry the reaction product in a vacuum oven at 80°C and 10 Pa for 24 h to obtain a monomer.
[0097] B2. Add 0.5g of nano zirconium oxide and 0.45g of 3-isocyanatepropyltrimethoxysilane to 20mL of ethanol and 8mL of deionized water, stir evenly, adjust the pH to 4 with 36% hydrochloric acid, stir and react at 40°C for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain pretreated wear-resistant aggregate.
[0098] B3. Add 2.5g monomer to 20mL N-methyl-2-pyrrolidone, stir evenly, add 0.2mL trifluoroacetic acid to promote monomer dissolution, heat to 80°C, add 0.5g pretreated wear-resistant aggregate, stir and react for 3h, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified wear-resistant aggregate.
[0099] B4. Add 2.6g of phosphoric acid to 30mL of ethanol and stir to obtain a phosphoric acid ethanol solution. Add 0.45g of calcium chloride dihydrate to 60mL of ethanol and stir at 25°C for 30min. Add 6.1g of triethylamine and stir for 10min. Add 30mL of phosphoric acid ethanol solution and stir to react for 12h. Collect the precipitate by centrifugation at 8000rpm. Wash the precipitate three times with ethanol to remove triethylamine and add it to 50mL of ethanol to form a stable emulsion to obtain calcium phosphate oligomer. Mix 30g of calcium phosphate oligomer and 2.5g of modified wear-resistant aggregate and stir well to obtain composite wear-resistant aggregate.
[0100] Comparative Example 3 The difference between this comparative example and Example 2 is that the monomer is not grafted onto the surface of the pretreated wear-resistant aggregate, and the remaining steps and raw materials are the same as those of Example 2.
[0101] B1. Add 0.5g of nano zirconium oxide and 0.45g of 3-isocyanatepropyltrimethoxysilane to 20mL of ethanol and 8mL of deionized water, stir evenly, adjust the pH to 4 with 36% hydrochloric acid, stir and react at 40°C for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain pretreated wear-resistant aggregate.
[0102] B2. Add 2.6 g of phosphoric acid to 30 mL of ethanol and stir to obtain a phosphoric acid ethanol solution. Add 0.45 g of calcium chloride dihydrate to 60 mL of ethanol and stir at 25°C for 30 min. Add 6.1 g of triethylamine and stir for 10 min. Add 30 mL of phosphoric acid ethanol solution and stir to react for 12 h. Collect the precipitate by centrifugation at 8000 rpm. Wash the precipitate three times with ethanol to remove triethylamine and add it to 50 mL of ethanol to form a stable emulsion to obtain calcium phosphate oligomer. Mix 30 g of calcium phosphate oligomer and 2.5 g of pretreated wear-resistant aggregate and stir well to obtain composite wear-resistant aggregate.
[0103] Comparative Example 4 The difference between this comparative example and Example 2 is that no calcium phosphate oligomer is added, and the remaining steps and raw materials are the same as those in Example 2.
[0104] B1. Add 5 g of dicyandiamide and 1.5 g of potassium hydroxide to 50 mL of 2-methoxyethanol, stir at 200 rpm for 10 min, add 2.7 mL of adiponitrile, raise the temperature to 125°C, stir and react for 6 h, filter the mixture and wash with methanol to obtain a reaction product, and dry the reaction product in a vacuum oven at 80°C and 10 Pa for 24 h to obtain a monomer.
[0105] B2. Add 0.5g of nano zirconium oxide and 0.45g of 3-isocyanatepropyltrimethoxysilane to 20mL of ethanol and 8mL of deionized water, stir evenly, adjust the pH to 4 with 36% hydrochloric acid, stir and react at 40°C for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain pretreated wear-resistant aggregate.
[0106] B3. Add 2.5g monomer to 20mL N-methyl-2-pyrrolidone, stir evenly, add 0.2mL trifluoroacetic acid to promote monomer dissolution, heat to 80°C, add 0.5g pretreated wear-resistant aggregate, stir and react for 3h, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain a composite wear-resistant aggregate.
[0107] Example 3 A polyether super wear-resistant halogen-free flame-retardant TPU composite material comprises the following raw materials in parts by mass: 90 parts of polyether thermoplastic polyurethane elastomer, 10 parts of the composite flame-retardant filler prepared in Example 1, 10 parts of the composite wear-resistant aggregate prepared in Example 2, 1 part of a compatibilizer, 0.1 parts of an ultraviolet absorber UV-P, and 0.2 parts of an antioxidant 300.
[0108] A method for preparing a polyether type super wear-resistant halogen-free flame-retardant TPU composite material comprises the following steps:
[0109] S1. Place a polyether thermoplastic polyurethane elastomer, a composite flame retardant filler, a composite wear-resistant aggregate, a compatibilizer, an antibacterial agent, an ultraviolet absorber UV-P, and an antioxidant 300 in a mixer, and mix at high speed for 3-5 minutes at 40-60°C to obtain a mixture;
[0110] S2. The mixed material is placed in a twin-screw extruder, and after extrusion and granulation, a polyether-type ultra-wear-resistant halogen-free flame-retardant TPU composite material is obtained, wherein the twin-screw extruder process is as follows: the temperature of the twin-screw feeding zone is 185°C, the temperature of the plasticizing zone is 195°C, the head temperature is 205°C, and the screw speed is 80rpm.
[0111] Example 4 A polyether super wear-resistant halogen-free flame-retardant TPU composite material comprises the following raw materials in parts by mass: 100 parts of polyether thermoplastic polyurethane elastomer, 13 parts of the composite flame-retardant filler prepared in Example 1, 11 parts of the composite wear-resistant aggregate prepared in Example 2, 1.5 parts of a compatibilizer, 0.3 parts of an ultraviolet absorber UV-O, and 0.4 parts of an antioxidant 168.
[0112] A method for preparing a polyether type super wear-resistant halogen-free flame-retardant TPU composite material comprises the following steps:
[0113] S1. The polyether thermoplastic polyurethane elastomer, the composite flame retardant filler prepared in Example 1, the composite wear-resistant aggregate prepared in Example 2, the compatibilizer, the ultraviolet absorber UV-O, and the antioxidant 168 are placed in a mixer and mixed at high speed for 3-5 minutes at 40-60°C to obtain a mixture;
[0114] S2. The mixed material is placed in a twin-screw extruder, and after extrusion and granulation, a polyether-type ultra-wear-resistant halogen-free flame-retardant TPU composite material is obtained, wherein the twin-screw extruder process is as follows: the temperature of the twin-screw feeding zone is 185°C, the temperature of the plasticizing zone is 195°C, the head temperature is 205°C, and the screw speed is 80rpm.
[0115] Example 5 A polyether super wear-resistant halogen-free flame-retardant TPU composite material comprises the following raw materials in parts by mass: 110 parts of polyether thermoplastic polyurethane elastomer, 15 parts of the composite flame-retardant filler prepared in Example 1, 12 parts of the composite wear-resistant aggregate prepared in Example 2, 2 parts of a compatibilizer, 0.5 parts of an ultraviolet absorber UV-9, and 0.6 parts of an antioxidant 1010.
[0116] A method for preparing a polyether type super wear-resistant halogen-free flame-retardant TPU composite material comprises the following steps:
[0117] S1. The polyether thermoplastic polyurethane elastomer, the composite flame retardant filler prepared in Example 1, the composite wear-resistant aggregate prepared in Example 2, the compatibilizer, the ultraviolet absorber UV-9, and the antioxidant 1010 are placed in a mixer and mixed at high speed for 4 minutes at 50°C to obtain a mixture;
[0118] S2. The mixed material is placed in a twin-screw extruder, and after extrusion and granulation, a polyether-type ultra-wear-resistant halogen-free flame-retardant TPU composite material is obtained, wherein the twin-screw extruder process is as follows: the temperature of the twin-screw feeding zone is 185°C, the temperature of the plasticizing zone is 195°C, the head temperature is 205°C, and the screw speed is 80rpm.
[0119] Comparative Example 5 The difference between this comparative example and Example 4 is that the composite flame retardant filler prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.
[0120] Comparative Example 6 The difference between this comparative example and Example 4 is that the composite flame retardant filler prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.
[0121] Comparative Example 7 The difference between this comparative example and Example 4 is that the composite wear-resistant aggregate prepared in Example 2 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.
[0122] Comparative Example 8 The difference between this comparative example and Example 4 is that the composite wear-resistant aggregate prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.
[0123] The performance of the polyether-type super wear-resistant halogen-free flame-retardant TPU composite materials prepared in Examples 3-5 and Comparative Examples 5-8 was tested;
[0124] Test of tensile strength and elongation at break: The prepared polyether super wear-resistant halogen-free flame-retardant TPU composite material was tested for performance according to the standard GB / T1040-2006, and the tensile strength and elongation at break of the sample were measured using an electronic tensile testing machine. The tensile speed was 50 mm / min.
[0125] Hardness test: Use Shore hardness tester for testing, test three sets of data for each sample and take the average value.
[0126] Flame retardant performance test: According to GB / T2408-2008 and GBT2406.1-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", the flame retardant performance of the polyether type super wear-resistant halogen-free flame retardant TPU composite material prepared above was tested.
[0127] Wear resistance test: The wear resistance of the polyether type super wear-resistant halogen-free flame-retardant TPU composite material prepared above was tested according to GB9867-88 standard, and the rotary drum abrasion machine method was used to record the wear amount (mg); the test results are shown in Table 1 below:
[0128]
[0129] It can be seen from the data in Table 1 that in Comparative Example 5, Co-Mn-O nanomaterials were not synthesized on the surface of calcium sulfate whiskers, and the prepared composite flame retardant filler was added to the polyether type super wear-resistant halogen-free flame retardant TPU composite material, and its mechanical properties and flame retardant properties decreased. This may be because the Co-Mn-O nanomaterial has good flame retardant properties, and the Co-Mn-O nanomaterial is synthesized on the surface of calcium sulfate whiskers, which increases the contact area between the composite flame retardant filler and the polyether type TPU composite material, and mechanically interlocks with the polyether type TPU composite material, and can exert good mechanical properties. However, the surface of the calcium sulfate whisker lacks Co-Mn-O nanomaterials, and this effect cannot be achieved, so the mechanical properties and flame retardant properties decrease;
[0130] Comparative Example 6 is a composite flame retardant filler prepared without adding the modified phytic acid-vanillin complex, and added to the polyether type super wear-resistant halogen-free flame retardant TPU composite material, and its mechanical properties and flame retardant properties are reduced. This may be because the modified phytic acid-vanillin complex is adsorbed into the pores of the Co-Mn-O nanomaterial in the modified calcium sulfate whisker, and forms an organic-inorganic flame retardant material with the modified calcium sulfate whisker, thereby improving the flame retardant properties, and the modified phytic acid-vanillin complex can be combined with the hydrophobic segment of the polyether TPU composite material to improve the flame retardant properties and mechanical properties of the polyether TPU composite material, while the modified calcium sulfate whisker lacks the bio-based flame retardant and the modified phytic acid-vanillin complex, and this effect cannot be achieved, so the mechanical properties and flame retardant properties are reduced;
[0131] In Comparative Example 7, the monomer was not grafted on the surface of the pretreated wear-resistant aggregate. The prepared composite wear-resistant aggregate was added to the polyether-type super wear-resistant halogen-free flame-retardant TPU composite material, and its wear resistance and mechanical properties decreased. This may be because the monomer was grafted on the surface of the pretreated wear-resistant aggregate, and the amino group contained in the monomer could be combined with the polyether TPU molecular chain through hydrogen bonding, so that the wear-resistant aggregate was evenly dispersed in the polyether TPU composite material, and the wear resistance was improved. The triazine ring structure contained in the monomer increased the rigidity of the molecular chain of the polyether TPU composite material and improved the mechanical properties. However, the composite wear-resistant aggregate lacked monomers and could not achieve this effect, so the wear resistance and mechanical properties decreased.
[0132] In Comparative Example 8, no calcium phosphate oligomers were added, and the prepared composite wear-resistant aggregate was added to the polyether type super wear-resistant halogen-free flame-retardant TPU composite material, and its wear resistance and mechanical properties decreased. This may be because the calcium phosphate oligomers can be combined with the molecular chains of the polyether TPU composite material through hydrogen bonds, making the polyether TPU composite material more compact, increasing the dissipation effect of external force, and having excellent wear resistance. The modified wear-resistant aggregate and the composite flame-retardant material can be coated in the polyether TPU composite material to improve the flame retardancy and high wear resistance of the polyether TPU composite material. However, the composite wear-resistant aggregate lacks calcium phosphate oligomers and cannot achieve this effect, so the wear resistance and mechanical properties decrease.
[0133] The data in Table 1 show that the polyether type super wear-resistant halogen-free flame retardant TPU composite materials prepared in Examples 3-5 meet the test performance requirements, while the polyether type super wear-resistant halogen-free flame retardant TPU composite materials prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the polyether type super wear-resistant halogen-free flame retardant TPU composite materials prepared by the present invention have good mechanical properties, flame retardant properties and wear resistance.
[0134] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0135] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A polyether type super wear-resistant halogen-free flame-retardant TPU composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of polyether thermoplastic polyurethane elastomer, 10-15 parts of composite flame retardant filler, 10-12 parts of composite wear-resistant aggregate, 1-2 parts of compatibilizer, 0.1-0.5 parts of ultraviolet absorber and 0.2-0.6 parts of antioxidant; The composite flame retardant filler is prepared by reacting phytic acid, vanillin and an organosilicon compound, and then mixing with modified calcium sulfate whiskers; The modified calcium sulfate whisker is prepared by mixing hydroxylated calcium sulfate whisker with a cobalt source and a manganese source and calcining the mixture; The composite wear-resistant aggregate is prepared by mixing modified wear-resistant aggregate and calcium phosphate oligomer; The modified wear-resistant aggregate is prepared by reacting dicyandiamide and adiponitrile to form a monomer, and then mixing and reacting with the wear-resistant aggregate surface-treated with isocyanate silane; The wear-resistant aggregate is selected from nano zirconium oxide.
2. A polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The hydroxylated calcium sulfate whisker has a length of 12-26 μm and a diameter of 0.5-1.5 μm.
3. The polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The manganese source is selected from manganese sulfate hydrate or manganese nitrate; the cobalt source is selected from cobalt sulfate heptahydrate or cobalt nitrate; the roasting temperature is 450-550° C., and the roasting time is 3-5 hours.
4. The polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The hydroxylated calcium sulfate whisker is specifically prepared by the following steps: adding the calcium sulfate whisker into a sodium phosphate tribasic solution with a concentration of 0.02-0.03 mol / L, ultrasonically treating, stirring evenly, filtering, washing and drying to obtain the hydroxylated calcium sulfate whisker.
5. The polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The isocyanate silane is selected from 3-isocyanate propyl trimethoxy silane or isocyanate propyl triethoxy silane.
6. The polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The compatibilizer is a hydroxyl-terminated polyether-modified silicone oil, and the hydroxyl-terminated polyether-modified silicone oil is XIAMETER OFX-3667; the antioxidant is selected from any one of antioxidant 300, antioxidant 168, antioxidant 1010, and antioxidant 626.
7. The polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The ultraviolet absorber is selected from any one of ultraviolet absorber UV-P, ultraviolet absorber UV-O, ultraviolet absorber UV-9 and ultraviolet absorber UV-531.
8. A method for preparing the polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Place a polyether thermoplastic polyurethane elastomer, a composite flame retardant filler, a composite wear-resistant aggregate, a compatibilizer, a UV absorber, and an antioxidant in a mixer, and mix at high speed for 3-5 minutes at 40-60°C to obtain a mixture; S2. The mixed material is placed in a twin-screw extruder, and after extrusion and granulation, a polyether-type ultra-wear-resistant halogen-free flame-retardant TPU composite material is obtained.
9. The method for preparing a polyether type super wear-resistant halogen-free flame-retardant TPU composite material according to claim 8, characterized in that: The twin-screw extruder process is as follows: the temperature of the twin-screw feeding zone is 180-190°C, the temperature of the plasticizing zone is 190-200°C, the head temperature is 200-210°C, and the screw speed is 70-90rpm.
Citation Information
Patent Citations
High-wear-resistance transparent TPU spherical film and preparation method thereof
CN104177817A
Preparation method of halogen-free flame-retardant thermoplastic polyurethane
CN104212155A